The cross gardener - Wright, Jason F. (Berkley Books, 2011)
Filled with sorrow over the fatal car accident of his wife and their unborn child, John Bevan erects a small cross near the scene of the accident and then withdraws from life and love. But when he encounters a young man kneeling before the cross, touching it up with white paint. John's conversations and travels with this mysterious man--known to him only as the Cross Gardener--forever change his world